Optimal infiltration depth threshold for low-temperature plasma ablation in fungal keratitis - Zhengwei Yang; Miaomiao Liu; Guihua Yang; Lijin Wen; Juan Yang; Hanqiao Li; Zhiwen Xie; Xie Fang; Shunrong Luo; Xianwen Xiao; Yuan Lin; Huping Wu (Journal of Ophthalmic Inflammation and Infection)
Abstract Purpose To identify prognostic factors and their optimal thresholds influencing the treatment outcome of low-temperature plasma ablation therapy in patients with fungal keratitis (FK). Methods The clinical information of fifty-one patients with FK treated with low-temperature plasma ablation at Xiamen Eye Center from 2018 to 2024 was retrospectively analyzed. Patients were categorized into Responder and Non-Responder groups based on their response to treatment: complete/partial healing (Responder group) versus disease progression or need for additional surgery (Non-Responder group). Differences in demographic and clinical characteristics between the two groups were compared. Additionally, exact univariate and multivariate logistic regression were performed to identify prognostic factors. Lastly, receiver operating characteristic (ROC) curve analysis was utilized to determine the cut-off value for significant prognostic factors. Results Among the 51 patients, 37 were classified in the Responder group and 14 in the Non-Responder group. Univariate analysis revealed significant differences in the presence of hypopyon (p = 0.038), ulcer size (p = 0.002), infiltration depth (p = 0.001), and paracentral ulcer location (p = 0.030) between the groups. Multivariate analysis identified infiltration depth (adjusted odds ratio [aOR] = 1.41, 95% CI: 1.05–1.91, p = 0.024) as the sole significant independent prognostic factor. ROC analysis demonstrated excellent discrimination ability for infiltration depth, with an area under the curve of 0.966. Finally, the optimal threshold for infiltration depth was determined to be 0.48, exhibiting a sensitivity of 92.86% and specificity of 91.89%. Conclusions Low-temperature plasma ablation represents an effective treatment for FK, with infiltration depth serving as a crucial prognostic indicator. The identified threshold provides valuable guidance for patient selection. Nonetheless, larger prospective studies are warranted to validate these findings.